2019
DOI: 10.5603/cj.a2018.0003
|View full text |Cite
|
Sign up to set email alerts
|

How does the risk of cardiovascular death and cardiovascular risk factor profiles differ between socioeconomic classes in Poland: A country in transition

Abstract: Background: Socioeconomic status (SES) is an important factor of cardiovascular diseases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Nevertheless, our results suggest that it is unlikely that the social gradient in CVD mortality observed in the Polish population can be explained by differences in access to health care and consequential differences in risk factors control. In the entire sample the prevalence of the main CVD risk factors (hypertension, current smoking, obesity, and dyslipidaemia) was higher in participants with low SES [6]. It seemed that the CVD risk factors could be more effectively controlled by people with higher SES due to higher health competences.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, our results suggest that it is unlikely that the social gradient in CVD mortality observed in the Polish population can be explained by differences in access to health care and consequential differences in risk factors control. In the entire sample the prevalence of the main CVD risk factors (hypertension, current smoking, obesity, and dyslipidaemia) was higher in participants with low SES [6]. It seemed that the CVD risk factors could be more effectively controlled by people with higher SES due to higher health competences.…”
Section: Discussionmentioning
confidence: 93%
“…Estimates of the Polish Government Population Council (Rządowa Rada Ludnościowa) not only show that groups with low education have higher CVD mortality rates, but also that the differences in mortality are increasing over time [4]. Two recent publications by Podolecka et al [5] and Nadrowski et al [6] confirmed strong negative relationships between SES and the prevalence of CVD risk factors as well as between SES and CVD risk measured as SCORE index in the Polish population. Higher education level was associated with a lower prevalence of hypertension, smoking, overweight, obesity, diabetes, and dyslipidaemia.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first nationwide study that focuses on the impact of socioeconomic and environmental factors, such as air pollution, on HF. Many previous studies reported a correlation between socioeconomic status and CVD risks [11,12]. Variation in the burden of HF is also likely caused by other-than-traditional factors.…”
Section: Discussionmentioning
confidence: 98%
“…Those with low SES have been found to have higher prevalence of CVD risk factors than those in higher SES groups in high-income countries, regardless of the particular indicators of SES used in the studies. 10 11 In contrast, both positive and negative associations between individual SES and prevalence of CVD risk factors have been uncovered in some low/middle-income countries. 12 13 However, there has been limited evidence on how clustering of CVD risk factors differs by individual SES.…”
Section: Introductionmentioning
confidence: 99%